Digital Labour and the Use-value of Human Work. On the Importance of Labouring Capacity for understanding Digital Capitalism - Sabine Pfeiffer (tripleC: Communication, Capitalism & Critique)
On the face of its virtual and immaterial appearance, digital labour often is seen as a phenomenon of abstract work. Contrary to that common understanding, in Marx’ theory the abstraction of labour derives from its historical development into a commodity, splitting human work as all commodities into use-value and exchange-value. Thus the process of abstraction is of economical logic, and not to be explained or characterized by the virtual and immaterial quality that is typical for the means and objects of digital labour. In his early work Marx differentiates between living labouring capacity (Arbeitsvermögen) as the use-value of human work and labour power as its objectified form to be exchanged. In the tradition of Marx‘ Grundrisse Oskar Negt and Alexander Kluge in Geschichte und Eigensinn pointed to the dialectical relationship between the use-value and exchange-value of labour, revealing how labour on its use-value side ‟contains and reproduces capacities and energies that exceed its realisation in/as commodity”, extending the model of labour power ‟to a whole range of physiological, sexual, social, and national relations” (Negt and Kluge 1993a, xxxiii). While these qualitative and material as well as corporeal aspects of human work are still visible in industrial production processes, they seem to be vanished in virtual work environments. But, digital capitalism not only opens up exploitation to higher levels and new forms (e.g. Fuchs 2012; Scholz 2012), the relevance of human work and its use-value for capitalism becomes more concealed to the same degree as it becomes more significant. The article develops an analytical conception relying on Marx‘ dialectical distinction between the use-value (labouring capacity) and the exchange-value (labour power), and transforming it into an operationalized model that could be and has been successfully used for empirical studies of digital labour. Labouring capacity has three levels of phenomena: subjectifying corporeal working action, material means and objects of work (even in virtual environments), and the socially and physically experienceable face of globalised work organisation. This analytical concept of labouring capacity (Arbeitsvermögen; Pfeiffer 2004) is especially helpful to reveal the dialectics in digital work and its sources of value creation (Pfeiffer 2013). The article unfolds the theoretical foundations of the concept, and elaborates its potential to analyse digital labour.